Intermediate and Transitory Inflammation Mediate Proper Alveolar Bone Healing Outcome in Contrast to Extreme Low/High Responses: Evidence from Mice Strains Selected for Distinct Inflammatory Phenotypes - Priscila Maria Colavite; Michelle de Campos Soriani Azevedo; Carolina Fávaro Francisconi; Angélica Cristina Fonseca; André Petenucci Tabanez; Jéssica Lima Melchiades; Daniela Carignatto Passadori; Andrea Borrego; Marcelo De Franco; Ana Paula Favaro Trombone; Gustavo Pompermaier Garlet (Biology)
Alveolar bone healing is influenced by various local and systemic factors, including the local inflammatory response. This study aimed to evaluate the role of inflammatory responsiveness in alveolar bone healing using 8-week-old male and female mice (N = 5/time/group) strains selected for maximum (AIRmax) or minimum (AIRmin) acute inflammatory response carrying distinct homozygous RR/SS Slc11a1 genotypes, namely AIRminRR, AIRminSS, AIRmaxRR, and AIRmaxSS mice. After upper right incisor extraction, bone healing was analyzed at 0, 3, 7, and 14 days using micro-computed tomography, histomorphometry, birefringence, immunohistochemistry, and PCRArray analysis. AIRmaxSS and AIRminRR presented the highest and lowest inflammatory readouts, respectively, associated with lowest repair levels in both strains, while intermediate inflammatory phenotypes observed in AIRminSS and AIRmaxRR were associated with higher repair levels in such strains. The better healing outcomes are associated with intermediate inflammatory cell counts, a balanced expression of pro- and anti-inflammatory cytokines and chemokines, increased expression of growth and osteogenic factors and MSCs markers. Our results demonstrate that extreme high and low inflammatory responses are not ideal for a proper bone repair outcome, while an intermediate and transitory inflammation is associated with a proper alveolar bone healing outcome.